Antioxidant polyethylene films based on a resveratrol containing Clay of Interest in Food Packaging Applications. (December 2015) - Busolo, M.A.; Lagaron, J.M.
Highlights: Resveratrol exhibited high thermal stability and strong antioxidant capacity when it was compared to the benchmark additive butylated hydroxytoluene (BHT). Active composites were manufactured by immobilization of resveratrol in the polymeric matrix and, also by montmorillonite modification with resveratrol prior to melt mixing with the polymer. The resulting composites not only showed strong antioxidant activity, but also antimicrobial activity. Resveratrol migration from composites to water and isooctane showed low levels in water (<0.01 mg/kg) and was not detectable in isooctane. Active films containing resveratrol could potentially extend the shelf-life of red meat over a few days by a mechanism of free radicals trapping. Abstract: The phenolic antioxidant resveratrol, which is naturally produced by plants under stress conditions, was seen to exhibit high thermal stability and strong antioxidant capacity in 2, 2-diphenyl-1-picrylhydrazyl (DPPH) assays. The antioxidant behavior was compared to the benchmark food contact permitted butylated hydroxytoluene (BHT). Active linear low density polyethylene (LLDPE) composites were manufactured by immobilization of resveratrol in the polymeric matrix and also by pre-incorporation of the resveratrol into a food contact permitted montmorillonite clay prior to melt mixing with the polymer. Migration tests from active films in water and isooctane showed extremely low migration levels in water (below 0.01 mg/kg) and was not detectable in isooctane. The resulting composites not only showed strong antioxidant activity, but also antimicrobial activity. The Thiobarbituric Acid Reactive Substances method (TBARS) was also applied to assess the comparative oxidative behavior in air of fresh meat in direct contact with the LLDPE film containing the active clay. The results suggested that this technology could potentially extend the shelf-life of red meat over a few days by a mechanism of free radicals trapping and the subsequent arrest in food oxidation processes.